Dare to Know by Thyself (Sapere Aude): The Legacy of the Enlightenment and Post Enlightenment in Working-Class Adult Education - Maria A Vetter (Adult Education Research Conference, 2019)
The Enlightenment and Post Enlightenment relationship to working-class adult education is examined in the case of the working class in Chile at the turn of the 20th century.
Keywords: Recabarren; Enlightenment; Post Enlightenment; Independent Working Class Education